Analysis of the Application of Digital Leadership to Improve Service Quality at Gresik Police Station - Ramadhan Nasution; Amril Muhammad (Journal of Social Research, 2023)
In an effort to improve the quality of services to the community in the era of the Industrial Revolution 4.0, the National Police has digitized various forms of services in accordance with the functions in the National Police, both operational, coaching and supporting functions. In this context, the National Police not only needs personnel who have competence in the digital field, but also leaders must also apply digital leadership models. The purpose of this study was to determine the digital leadership of the Gresik Police Chief. The research used a qualitative approach. Data collection was carried out by observation, interviews with key, key and supporting informants and supplemented by document studies. Data analysis using models from Miles and Huberman. Data credibility is done by triangulation techniques. Research findings show that digital leadership applied by the leadership of the Gresik Regional Police includes aspects of: inspiring others, using technology (leverages technology), encouraging collaboration, encouraging innovation, and managing risk.